2016
DOI: 10.1007/s00737-016-0648-y
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum bonding: the impact of maternal depression and adult attachment style

Abstract: Maternal depression poses a risk for the developing mother-infant relationship. Similarly, maternal insecure attachment styles may limit the ability to adequately connect with the newborn during the postpartum period. The aim of this study was to investigate the effect of maternal depression and insecure attachment (insecure and dual/disorganized) on maternal bonding in a sample of n = 34 women with depression according to DSM-IV and n = 59 healthy women. Maternal depression was assessed 3 to 4 months postpart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
79
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 42 publications
14
79
0
2
Order By: Relevance
“…The mediating role of depression symptoms in the association between anxious attachment style and infant‐focused anxiety bonding conforms with reliable observations that anxious attachment is more frequently associated with PPD symptoms than is the avoidant attachment style (Warfa, Harper, Nicolais, & Bhui, ). These findings also are in line with Nonnenmacher et al.’s () report, but differ from Chrzan‐Dętkoś and Łockiewicz (), who found an association between insecure attachment and EPDS, but not bonding. Further, consistent with a reported association between CR‐PTSD symptoms and avoidant attachment style (Ayers et al., ), our findings add a unique role for CR‐PTSD symptoms in the association between avoidant attachment style with cognitions of anger and rejection toward the infant.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The mediating role of depression symptoms in the association between anxious attachment style and infant‐focused anxiety bonding conforms with reliable observations that anxious attachment is more frequently associated with PPD symptoms than is the avoidant attachment style (Warfa, Harper, Nicolais, & Bhui, ). These findings also are in line with Nonnenmacher et al.’s () report, but differ from Chrzan‐Dętkoś and Łockiewicz (), who found an association between insecure attachment and EPDS, but not bonding. Further, consistent with a reported association between CR‐PTSD symptoms and avoidant attachment style (Ayers et al., ), our findings add a unique role for CR‐PTSD symptoms in the association between avoidant attachment style with cognitions of anger and rejection toward the infant.…”
Section: Discussionsupporting
confidence: 86%
“…Research on factors that influence parental, specifically maternal, emotions toward her infant has flourished in recent decades, with greater focus on psychiatric symptoms that negatively impact bonding. As the incidence of postpartum depression (PPD) ranges between 10 to 20% (Brockington, ; Brummelte & Galea, ), the influence of PPD on maternal behaviors in general (e.g., O'Hara & McCabe, ) and bonding in particular is one of the most researched topics (Brockington, Fraser, & Wilson, ; Loh & Vostanis, ; Nonnenmacher, Noe, Ehrenthal, & Reck, ), demonstrating that depressed mothers express greater hostility and less responsiveness toward their infant, and are more likely to neglect or abuse their infant (reviewed in O'Hara & McCabe, ). Childbirth‐related posttraumatic stress disorder (CR‐PTSD) occurs in 1 to 6% of births (Alcorn, O'Donovan, Patrick, Creedy, & Devilly, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An APN working with a family directly after birth has the opportunity to observe signs of impaired bonding and begin assistance in promoting a positive bond. The APN must understand that "consistent attachments are crucial for the formation of close bonds to the infant" (p. 932) [29].…”
Section: Impact On Advanced Nursing Practicementioning
confidence: 99%
“…A mother's own attachment and quality of her own early family relationships may also be important in understanding the relationship between PND and parenting (7). This was further explored in two recent studies;, the first showing maternal depression mediated the relationship between maternal attachment style, as measured on the Attachment Style Interview, and the quality of the mother-infant bond (8). While the second study found a woman's own insecure attachment, measured using the Attachment Style Questionnaire in pregnancy, increased her risk of depression in the postpartum period (9).…”
Section: From Pregnancy To Early Childhoodmentioning
confidence: 99%